DINAMIKA HUKUMAN RAJAM DI BEBERAPA NEGARA MUSLIM MODERN DAN RELEVANSI PENERAPAN DI INDONESIA - Ilhami, Hanif A'la; Efendi, Zul (Jurnal AL-MAQASID: Jurnal Ilmu Kesyariahan dan Keperdataan, 2024)
This research aims to examine the implementation of stoning punishment in several Muslim countries and investigate the relevance of stoning punishment for implementation in Indonesia. This study is a qualitative research with a literature review approach by collecting books, articles, and legal documents related to the implementation of stoning punishment in modern countries. The research findings indicate that stoning punishment has been legislated in the laws of Brunei Darussalam. While Malaysia and Indonesia are still engaged in academic discourse and debates, Saudi Arabia and Iran, which initially acknowledged the existence of stoning punishment in their judiciary, are slowly abandoning it. Two factors reducing the enforcement of stoning punishment are identified. First, the increasing strength of discourse opposing the death penalty and even opposing the criminalization of adultery itself as it is considered a private matter. Second, the growing dominance of Western countries over the economy of Muslim countries resulting in their limited autonomy in determining their own laws. As for stoning punishment, from various approaches, it is relevant to be implemented in Indonesia because it can resolve various state budget issues and provide a more deterrent effect. Furthermore, stoning punishment is not exclusively Islamic law but also recognized in Judaism and Christianity, making it suitable for many religions in Indonesia.